2019
DOI: 10.3747/pdi.2018.00098
|View full text |Cite
|
Sign up to set email alerts
|

Extended Experience in the Use of Antibiotic Lock for Eradication of Biofilm Bacteria on Tenckhoff Catheter

Abstract: Whilst antibiotic lock is effective to eradicate biofilm bacteria on hemodialysis catheters, this adjunctive method has scarcely been tested in peritoneal dialysis (PD) patients. After our previous successful experience of its use to salvage two Tenckhoff catheters, we encountered another patient with problematic biofilm-associated PD peritonitis who strongly refused catheter removal. As a result, antibiotic lock was given once daily, initially, with continuation of the usual PD schedule. However, relapsing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Fourth, we cannot exclude spill of the amphotericin B catheter lock into the peritoneal cavity. 12 IP amphotericin B is associated with persistent leucocytosis and abdominal pain due to local chemical irritation attributed to the sodium desoxycholate solvent. 13,14 However, concentrations of IP amphotericin B used in previous studies are higher than the concentration in case of spill of amphotericin B using our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we cannot exclude spill of the amphotericin B catheter lock into the peritoneal cavity. 12 IP amphotericin B is associated with persistent leucocytosis and abdominal pain due to local chemical irritation attributed to the sodium desoxycholate solvent. 13,14 However, concentrations of IP amphotericin B used in previous studies are higher than the concentration in case of spill of amphotericin B using our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Such infections arise from bacterial adhesion to biomaterial surfaces with subsequent formation of antibiotic-refractory biofilms that are challenging to handle with in situ intraperitoneal antibiotics. Ex vivo studies of PD catheters removed from patients experiencing peritonitis showed that such catheters are covered by microbial biofilms usually composed of a single species or mixed microbial populations ( 8 10 ). The abundant extracellular polymeric matrix embedding these microbial communities leads to inadequate penetration into biofilms of standard intraperitoneal antibiotics, resulting in a high rate of relapsing infections which are treated only by catheter removal.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the field of catheter-related infections have focused on the use of antibiotic lock treatment as a therapeutic option for intravascular catheter-related infections. Currently, only a few studies have investigated the effects of lock therapy on microbial biofilms in PD ( 8 10 ). In hemodialysis, antimicrobial lock solution has been proven to be such an effective adjunctive treatment for biofilm-associated central venous catheter-related infections ( 11 14 ) that lock solution is nowadays the recommended rescue procedure for colonized intravascular catheters ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also the relative imperfection of the connective systems and catheters for the PD that undoubtedly creates a known risk of contamination of the abdominal cavity should be taken into consideration. At the same time, in the pathogenesis of recurrent peritonitis, a special role is given to the so-called "biofilm", that is, the composite formation from the cells of microorganisms and fibrin, which over time covers the walls of the peritoneal catheter [18].…”
mentioning
confidence: 99%